Synthesis and in vitro antiproliferative and antibacterial activity of new thiazolidine-2,4-dione derivatives - Nazar Trotsko; Agata Przekora; Justyna Zalewska; Grażyna Ginalska; Agata Paneth; Monika Wujec (Taylor & Francis Group, 2018)
In our present research, we synthesised new thiazolidine-2,4-diones (12-28). All the newly synthesised compounds were evaluated for antiproliferative and antibacterial activity. Antiproliferative evaluation was carried out using normal human skin fibroblasts and tumour cell lines: A549, HepG2, and MCF-7. The IC50 values were determined for tested compounds revealing antiproliferative activity. Moreover, safety index (SI) was calculated. Among all tested derivatives, the compound 18 revealed the highest antiproliferative activity against human lung, breast, and liver cancer cells. More importantly, the derivative 18 showed meaningfully lower IC50 values when compared to the reference substance, irinotecan, and relatively high SI values. Moreover, newly synthesised compounds were screened for the bacteria growth inhibition in vitro. According to our screening results, most active compound was the derivative 18 against Gram-positive bacteria. Therefore, it may be implied that the novel compound 18 appears to be a very promising agent for anticancer treatment.